The Impact of Banking Architecture Policy and Macroeconomic Condition on Indonesian Banking Concentration and Market Structure - Asngari, Imam; Marwa, Taufiq; Susetyo, Didik; Suhel, Suhel; Kadir, Syamsurijal A. (International Journal of Economics and Financial Issues, 2018)
This research discusses the concentration, market structure, and factors affecting the market structure of banking industry in Indonesia. The purpose of the study is to examine and analyze the impact of IBA Policies and macroeconomic conditions on the market structure of banking industry. Analytical techniques use concentration ratios and panel data regression models to analyze the determinants of the market structure of the banking industry. The market structure is measured by the ratio of banking asset concentration. Data used in this study are from 2004 until 2015. Bank balance sheets data of 109 conventional banks published by Bank Indonesia and the Financial Services Authority. Data on economic growth and inflation were published by the Central Bureau of Statistics. Based on the ratio of CR4 and CR8 concentration, it is found that the Indonesian banking market structure is monopolistic competition. Market structure is effectively and significantly influenced by banking regulatory factors, IBA consolidation policies, behavior and performance, bank size, market share, cost efficiency, inflation and economic growth. Keywords: consolidation, banking concentration, monopolistic competition, macroeconomic conditions. JEL Classifications: E52, E58, L1, L8